Correlation between the response to Mycobacterium tuberculosis antigens and the tuberculin skin test in patients with Rheumatoid Arthritis in Colombia (2013)
ABSTRACT: Introduction. Rheumatoid arthritis patients under treatment with anti-TNF-α are at a high risk of developing active tuberculosis, and therefore, screening for latent tuberculosis infection is recommended before anti-TNF-α therapy. Objective. To compare the tuberculin test and IFNγ production induced by culture filtrate proteins (CFPs) and Mycobacterium tuberculosis-specific CFP-10 antigens in rheumatoid arthritis patients. Materials and methods. An analytic transversal study was conducted in rheumatoid arthritis patients treated at Hospital Universitario San Vicente Fundación between January and December 2007. IFNγ production in response to CFPs and CFP-10 was measured in the supernatants of whole blood cultures and evaluated for correlations with tuberculin reactivity. The degree of concordance between both tests was also established. Results. Forty-five patients were included, of which 14 (31.1%) had a tuberculin reaction of ≥10 mm of induration, 9 (20%) produced IFNγ in response to CFP-10, and 7 were positive for both tests. The correlation between tests was r=0.53 (IC 95%:0.28-0.72), and the global concordance between tests was 80%, with a Kappa coefficient of 0.48 (IC95%:0.20-0.76). Conclusions. Only two tuberculin (-)/CFP-10+ “anergic” patients were observed. By contrast, six tuberculin +/CFP-10(-) “tuberculin false-positive” patients were observed. These data suggest that the tuberculin test is not an appropriate tool for determining the need for tuberculosis prophylaxis.